The sweet seduction of Atahualpa’s gold: betrayals and disagreement concerning the voracity of the lagoons in Cajamarca, Peru - Peñafiel, Adriana Paola Paredes (Anuário Antropológico, 2023)
Relationships among the peasants and the lagoons in rural communities situated in the northern Andes in Peru are ambiguous. The lagoons, located at the top of the mountains, appear as ferocious entities in the stories of local people. However, when these waters were threatened by a mining project, the peasants defended these lagoons with their own lives. This work aims to analyse narratives concerning the metamorphosis of humans when they are seduced by these lagoons. The paper is based on ethnographic research conducted between 2013 and 2014 in the village of El Tambo, in the district of Bambamarca, Hualgayoc Province, and the town of Celendín, Celendín Province. Both localities are within the region of Cajamarca in the Peruvian Andes. Besides this period of research, new reports and testimonies were collected in both localities during short visits between 2016 and 2020. Certain categories, like wild/tame, sweet/savoury, voracious/self-controlled, are essential to the analysis in order to understand the relationship between the seduction of the beings that inhabit the lagoons and the repudiation of the voracity of open-pit mining.